Strategi Pengembangan Kreativitas Dan Inovasi Ibu Rumah Tangga Melalui Kampung Guyub Rukun RW 02 Kelurahan Rungkut Kidul - Firly Dwi Ainur Rochmah; Nurhadi Nurhadi (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
Empowering MSMEs is crucial for boosting the national economy in the contemporary industrial revolution age. The methods for fostering invention and creativity among housewives in RW 02, Rungkut Kidul Village, are covered in this study. Housewives contribute to the family's financial stability. Women labor to obtain economic stability in the face of uncertain economic situations. And MSME performers make up the bulk of the female cast. By incorporating digital marketing into their product offerings, MSME actors based in RW 02 Rungkut Kidul are attempting to raise the caliber of their output. Furthermore, the bulk of business owners have implemented business legitimacy, MSME actors. But there's a problem: only a small percentage of MSMEs have.